Microplastic Fighters: Building a Zero Waste Generation through Student Education and Action in Plastic Waste Management on the Bungus Teluk Kabung Coast - Sandi Fransisco Pratama; Threo Wanda Marten; Dwi Happy Anggia Sari; Fitri Olvia Rahmi; Nabila Sulaeman; Husnul Khotimah; Ganda Hijrah Selaras; Defni Yannita (Pelita Eksakta, 2026)
The Microplastic Fighters program was developed to increase elementary school students' understanding of the dangers of microplastics and waste management skills through experience-based learning methods. The activities were carried out systematically through the stages of socialization, training, technology application, mentoring, and evaluation. The results show an increase in the average knowledge score of students from 6.48 (pretest) to 7.84 (posttest). This increase in scores shows that the educational and interactive approach applied has proven effective in increasing student participation, creative thinking, and practical skills. Thus, this program has the potential to shape an environmentally conscious zero-waste generation and serve as an applicable educational strategy in supporting sustainable environmental conservation in coastal areas.